Study of natural frequencies of natural rubber cored novel sandwich structure without tip mass. (December 2020) - Gupta, Krishanu; Bhattacharjee, Biplab; Kumar Gupta, Sonu; Chakraborti, Prasun
Abstract: One of the important forms of smart structure available for various applications in engineering fields is Sandwich beams, for the reason that of variable applications, the capability to withstand at variable loading conditions, significant elastic retaining properties when in comparison to conventional structures. The basic of the present study is to investigate natural frequency ranges for a type of sandwich beam that has been manufactured using natural rubber (NR) that is indigenously available in Tripura, India, in combination to skin material of aluminium alloy 1050 grade. The present article deals with the study of free vibrational characteristics of cantilever sandwich panels (SwPs) with various skin thicknesses. A mathematical approach had been carried out using a standard platform for validating the results obtained from the analytical method. Also, experimentation had been conducted on sample of sandwich panels using Hammer test process and the natural frequencies of the same were obtained. It was found that the results obtained from the analytical method using a standard platform have been in good agreement with the other approach.